Regime Choice Determinants - The GCC Single Currency - Ghada Gomaa A. Mohamed; Manuchehr Irandoust (Current Aspects in Business, Economics and Finance Vol. 1, 2022)
The paper investigated theoretically and empirically the feasibility of the alleged potential monetary union among the six Gulf Cooperation Council members—the United Arab Emirates, the State of Bahrain, the Kingdom of Saudi Arabia, the Sultanate of Oman, the State of Qatar, and the State of Kuwait—before 2010. According to the theoretical model, the optimal foreign regime should maximize oil revenues while maintaining internal and external balances. This was shown to happen at the highest possible predicted foreign-exchange rate or the lowest possible level of uncertainty and volatility in foreign-exchange rate markets. Calculations employing a calibrated model revealed that if the GCC countries had chosen a foreign policy pegged to the SDR, the planned monetary union would likely result in economic advantages.